Open to Better? Teachers' Perceptions of Curriculum Integration in the Erasmus Mundus PETaL Master's Degree - Natividad Aguayo-Arrabal; María-Elena (Springer, 2022)
Erasmus Mundus Joint Master's Degrees (EMJMD) offer a unique opportunity to jointly design and deliver an integrated curriculum of excellence in an international context. This study analyses the case of a Master's Degree specialised in Education: PETaL "Play, Education, Toys and Languagesˮ. This is the first EMJMD obtained by the University of Cordoba (Spain) within the framework of the Erasmus+ Program (2014-2020), in coordination with the Polytechnic Institute of Lisbon (Portugal) and Marmara University (Turkey). Through the design, validation and distribution of an online questionnaire, this research aims to examine teachers' opinions on the place of integration in their teaching, as well as on the level of interdisciplinarity in the programme based on Harden's model ($). This pioneering course represents a favourable context in which to evaluate the "jointnessˮ in the curriculum and other aspects of the teaching-learning process, little explored so far in this context. The results reveal that, foreseeably, the conditions for greater integration in the successive editions are in place. Thus, it is necessary to continue strengthening teaching coordination and the aspects leading to further curricular integration. The study also serves as a reflection on teaching practice and the possibilities for interdisciplinarity in postgraduate education.